The Impact of Artificial Intelligence Utilization on Work Efficiency and Productivity of Secondary School Teachers - Chandra Satria Rochmad; Irfan Nasar; Mochamad Mujiono (Ihsan Cahaya Pustaka, 2025)
This study aims to explore the impact of artificial intelligence (AI) implementation on work efficiency and productivity of secondary school teachers. The research employed a descriptive approach combining quantitative and qualitative methods, involving 100 teachers in Bandung who participated through online questionnaires and in-depth interviews via Zoom. The findings reveal that the use of AI significantly helps reduce administrative workload, accelerates lesson planning processes, and facilitates more accurate and consistent student assessment. However, some teachers highlighted challenges, such as ethical concerns regarding data use, student privacy protection, and the risk of over-reliance on technology. Overall, AI serves as a supportive tool that enhances teachers’ work efficiency without replacing their professional roles. This study emphasizes the importance of improving digital literacy, adaptive skills, and teacher readiness in the technology-based learning era to ensure that AI implementation is effective and sustainable.